Technical And Non-Technical Effect Of Disaster That Are Relevant To Disaster Risk Management Cycle (DRMC) - Basri, Siti Aisyah Ahmad
Disaster is a hazard that has caused heavy loss of life, properties and livelihood. Every year, our country has been affected by disaster, whether natural disaster or manmade disaster. Disaster risk management is a management of resources and responsibility for dealing with all aspect of emergency. An effective disaster risk management requires the combination of knowledge and skills. Disaster Risk Management Cycle (DRMC) is a part of the important efforts which was designed to handle disaster risk. DRMC contains of four phases which are response, recovery, mitigation and preparedness. In this study, the effects of disaster were classified into technical effects and non-technical effect. Technical effects were focused on building structure, maintenance and safety while non-technical effects were focused on economic losses, cost of reconstruction, refurbishment and health. This paper aimed to determine the awareness of project members on DRMC in construction project. Besides, it was also to explore the disaster risk management and related risk that were relevant to a construction project. Questionnaires were distributed to the construction industry players and flood victims. The result obtained based on the survey revealed that majority of respondents did not aware about DRMC. In addition, it was discovered that in each phase of DRMC, both professional and non-professional respondent had different opinion on disaster management as presented by the hierarchy of the types of disaster risk management and the effects of disaster.